Stomach data from pelagic research survey bring new information in cod feeding pattern in the South-Western Baltic sea - Maioli, Federico (SLU/Dept. Of Aquatic Resources, 2019)
Pelagic and demersal cod (Gadus Morhua) specimens were collected respectively during a pelagic and a demersal survey in the Eastern Baltic sea in the fourth quarter of the years 2015-2017. Stomach contents were analysed and compared for the purpose of evaluating differences in the diet among pelagic and demersal specimens. Furthermore, generalized additive models (GAMs) were employed to investigate the daily fluctuations of stomach content weights of this predator. My results showed significant differences in the diet composition of demersal and pelagic cod mainly attributable to the higher weight share of sprat in the pelagic stomachs. Moreover, a remarkable diel variation in the stomach contents weights was present, indicating morning and evening peaks. The present study furnished novel insights into cod feeding pattern in the South-Western Baltic Sea. The implications of these findings for stock assessment multispecies models are also briefly discussed.